Bilateral Candida endophthalmitis accompanying Candida lusitaniae bloodstream infection: A case report. Issue 2 (February 2018) - Yamamoto, Shinya; Ikeda, Mahoko; Fujimoto, Fumie; Okamoto, Koh; Wakabayashi, Yoshitaka; Sato, Tomoaki; Tatsuno, Keita; Kaburaki, Toshikatsu; Yoshida, Shuntaro; Okugawa, Shu; Koike, Kazuhiko; Moriya, Kyoji
Abstract: Candida lusitaniae is an uncommon cause of candidiasis in humans. Ocular manifestations of C. lusitaniae infection have not been reported. C. lusitaniae is either intrinsically resistant to amphotericin B or can acquire such resistance. We describe a case of bilateral endophthalmitis due to C. lusitaniae bloodstream infection in a liver transplant patient with rectal cancer. The patient suffered fungemia and endophthalmitis and was treated with liposomal amphotericin B. The isolate was identified as C. lusitaniae by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, the system based on biochemical tests, and sequencing of the internal transcribed spacer region. The minimal inhibitory concentrations were 0.06 μg/mL for amphotericin B and 2.0 μg/mL for fluconazole. Repeat blood cultures were negative and the endophthalmitis improved following treatment with liposomal amphotericin B. However, the treatment was changed to fluconazole due to nephrotoxicity. No recurrence occurred after completion of treatment.